SURGICAL TACTICS IN COMPLICATED FORMS OF LIVER ECHINOCOCCOSIS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The results of treatment of 328 (51.4%) patients with liver echinococcosis are presented. The use of the ultrasonic dissector of the SONOCA 300 aspirator makes it possible to make wider use of radical modern methods of surgical interventions for echinococcosis, to perform them bloodlessly, with good final aero-, hemo- and cholestasis with minimal tissue trauma in the affected area. The developed algorithms for choosing tactics for surgical treatment of echinococcosis, taking into account an integrated approach to the choice of access, mainly to radical echinococcectomy and elimination of the residual cavity, as well as preventive chemotherapy, made it possible to improve the quality of care provided by reducing the frequency of immediate postoperative complications from 14.3% to 3.7 % (p=0.027 by χ2 criterion) and disease relapse from 13.4% to 2.8% (p=0.031 by χ2 criterion).